Influência de características físicas, químicas e mineralógicas de dois latossolos na movimentação de diesel e biodiesel - Rodrigo Trindade Schlosser (2017)
Because of the large soil and groundwater contamination by petroleum products, studies to better understand the process of contaminants movement and interaction with the porous media are important to assist in environmental diagnostics and to take the best option in control and remediation techniques. In this context, this study purpose was to evaluate influence of a Ferralsol oxisol (LF) and a Red-Yellow Oxisol (LVA) characteristics in the diesel, biodiesel and their different mixtures behavior in this porous media. The study was divided in four stages: (i) water solubility quantification, under compounds present in different diesel/biodiesel mixtures agitation; ii) diesel/biodiesel sorption capacity determination in the mentioned soils under water saturation different degrees in dynamic environment and by batch equilibrium tests; iii) water dissolved contaminants transport evalution in the studied soils. The results presented a linear behavior between the concentration in the dissolved organic carbon (DOC) soluble fraction and the proportion of biodiesel in the diesel, however, with no noticeable influence of the proportions of water dilution and DOC concentration in the solutions, with the exception of the 1:1 dilution. There was a reduction in the fuels retention capacity (RC) in both oxisols with the soil initial saturation level increase, being that the LVA provided fuels higher RC than the LF due to its higher content of organic matter, silt and clay, among other factors. In the freephase movement tests, a higher rate of infiltration/percolation and diesel and biodiesel higher conductivity were observed in LF than in LVA, besides initial saturation degree direct influence with soil water in both soils. From the batch equilibrium method, no success was obtained in the separation of absorbed and adsorbed phases from the fuels, however, it was verified that the initial saturation degree with water in the soil samples influenced considerably the diesel and biodiesel free phases sorption, being the LVA more sorptive than LF. Finally, the column tests presented that the LF Retardation Factor (R) was close to 3 being not possible to obtain the Rvalue in the LVA because of its high soluble fraction retention capacity.